Enterprising states : - Considine, Mark (Cambridge University Press, 2001)
This book explores two fundamental shifts in the paradigms of governance in Western bureaucracies: the widespread use of privatization, private firms and market methods to run core public services, and the conscious attempt to transform the role of citizenship from ideals of entitlement and security to new notions of mutual obligation, selectivity and risk.